Diagnostic value of miR-193a-5p in severe pneumonia and its correlation with prognosis - Xiaoji Su; Lijuan Zhu; Jiajia Zhuo; Shihai Zhang (Journal of Cardiothoracic Surgery)
Abstract Background Severe pneumonia is a common disease in children, with rapid progression and easy complications of respiratory failure, endangering the lives of children. This study aimed to elucidate the clinical significance of miR-193a-5p in severe pneumonia and to provide a new biomarker for the disease. Methods A total of 150 children with severe pneumonia and an equal number of healthy children were selected for analysis. Serum miR-193a-5p levels were detected by RT-qPCR. The correlation of miR-193a-5p with CRP, WBC, neutrophil count, and NLR was assessed by Spearman analysis. The diagnostic and prognostic value of miR-193a-5p in severe pneumonia was analyzed using ROC curves. The relationship between miR-193a-5p and the prognosis of severe pneumonia was evaluated using the Kaplan-Meier curve and a multivariate logistic analysis. Results Serum levels of miR-193a-5p were markedly elevated in children with severe pneumonia and exhibited a positive correlation with CRP, WBC, neutrophil count, and NLR. miR-193a-5p could effectively distinguish children with severe pneumonia from healthy children, with an AUC, sensitivity, and specificity of 0.862, 70.67%, and 88.67%, respectively. Serum miR-193a-5p expression was increased in children with poor prognosis and had a predictive value for patient prognosis. High expression of miR-193a-5p was linked to survival in children with severe pneumonia and was a risk factor for adverse prognosis. Conclusion Serum levels of miR-193a-5p were markedly elevated in children with severe pneumonia, which may be of significance for the early diagnosis of the disease and prognostic assessment.